“Social Justice Needs to Be Everywhere”: Imagining the Future of Anti-Oppression Education in Teacher Preparation - Kelly, Deirdre M.; Minnes Brandes, Gabriella (Alberta Journal of Educational Research, 2011)
This article analyzes a social-justice teacher education project in a larger teacher education program in Western Canada. This program-within-a-program took an anti-oppressive education approach designed to help teacher candidates to understand and challenge various forms of inequity and their interconnections. We review the social justice project first, through a descriptive analysis of our teaching, and second, through hour-long qualitative, semistructured interviews with 20 graduates of our program (all beginning teachers). Our alumni provided examples of teaching against the grain and also spoke to the challenges of implementing critical pedagogies. We conclude by providing four key recommendations and reflecting on the implications for future teacher preparation. Cet article analyse un projet de justice sociale dans le cadre d’un important programme de formation des enseignants dans l’Ouest canadien. Ce « programme à l’intérieur d’un programme » a adopté une approche pédagogique contre l’oppression, conçue pour aider les étudiants en pédagogie à comprendre et à remettre en question diverses formes d’iniquité et les liens entre elles. Nous nous penchons sur le programme de justice sociale, d’abord par une analyse descriptive de notre enseignement, ensuite par des entrevues qualitatives et semi-structurées d’une heure auprès de finissants de notre programme (tous débutant leur carrière d’enseignant). Nos anciens ont fourni des exemples d’enseignement à contre-courant et ont évoqué les défis liés à la mise en oeuvre de pédagogies critiques. Nous concluons en présentant quatre recommandations clés et en réfléchissant aux conséquences pour la formation des enseignants à l’avenir.